2019
DOI: 10.1055/s-0039-1688823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implementing Quantitative Blood Loss Assessment at the Time of Delivery

Abstract: Objective To evaluate the ability of estimated blood loss (EBL) and quantitative blood loss (qBL) to predict need for blood transfusion in women with postpartum hemorrhage (PPH). Study Design This is a retrospective chart review that identified women with PPH (>1,000 mL for vaginal or cesarean delivery) between September 2014 and August 2015, reported by EBL (n = 92), and October 2015 and September 2016, reported by qBL (n = 374). The primary metric was the area under the receiver-operating char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Our assumption of a 10% PPH rate was based on a previous study that was conducted from our institution. 17 We suspect that PPH rates were higher in this study than the previous study because we only included women undergoing cesarean delivery, whereas the previous study included women who had vaginal and cesarean deliveries. It is well known that cesarean delivery is associated with an increased risk of PPH compared with vaginal delivery.…”
Section: Results In Contextmentioning
confidence: 83%
See 1 more Smart Citation
“…Our assumption of a 10% PPH rate was based on a previous study that was conducted from our institution. 17 We suspect that PPH rates were higher in this study than the previous study because we only included women undergoing cesarean delivery, whereas the previous study included women who had vaginal and cesarean deliveries. It is well known that cesarean delivery is associated with an increased risk of PPH compared with vaginal delivery.…”
Section: Results In Contextmentioning
confidence: 83%
“…Data were obtained by chart review and abstraction of outpatient, Labor and Delivery, and anesthesia records. Assuming a 10% rate of PPH 17 and a 10% incidence of mild thrombocytopenia, a total of 2759 women (2508 with normal platelet count and 251 women with mild thrombocytopenia) would be needed to detect 60% difference in the risk of PPH with alpha of 0.05 and beta of 0.80. For statistical analysis, we used the chi-square test to analyze categorical variables and Student's t test or Wilcoxon rank-sum test for continuous variables.…”
Section: Methodsmentioning
confidence: 99%
“…14 A published review found that bimanual uterine compression could be used to stop or slow bleeding in cases where uterotonics were not effective in stopping PPH. 6,15 WHO recommends uterine compression as a measure to manage blood loss postvaginal delivery until proper medical care and support becomes available. 8…”
Section: Discussionmentioning
confidence: 99%
“…It is worth recognizing that recent publications have highlighted limitations of the clinical utility of QBL to predict change in hemoglobin or need for transfusion, indicating that QBL is not a perfect process or solution. 19,20 The authors would argue that prior works demonstrating the inaccuracy of estimation and the dangers of delay in hemorrhage management greatly outweigh the limitations of QBL. Best practices for transfusion indicate decisions should incorporate real-time measures of hemodynamic stability, such as the vital signs, urine output, and patient's mental status.…”
Section: Discussionmentioning
confidence: 99%